ANALISIS PENERIMAAN PAJAK ATAS BUMI DAN/ ATAU BANGUNAN PADA KECAMATAN LAREH SAGO HALABAN - Yolanda Dizza; Basri Mutia Yesi; Hanif Afriana Rheni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research purpose is to observe low acceptance of Rural and Urban Land or Building Tax receipts in Lareh Sago Halaban District. The method used in this research is qualitative research with the purpose to explain a phenomenon in depth through data collection, interviews, and observations. The technique used in choosing the population is the snowball sampling method from the Head of Finance. Triangulation is used to test the validity of the data by comparing each research method, which means the result of the interview compared to observation, then compared to the data. from the result of interviews, observation, and documentation it is known that low acceptance of Rural and Urban Land and Building (PBB P2) in Lareh Sago Halaban District is caused by the error in tax payable notification letter, taxpayer's economic factors, lack of tax payer's awareness, inappropriate tax collection wages, overlapping tax policies, and data reporting errors.keywords : Therefore, to increase Rural and Urban and Building Tax Revenues (PBB P2), local governments need to set the right policies.